PEMANFAATAN HALAMAN SEKOLAH SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Putri, Restuning Ropika (JURNAL BIOSHELL, 2012)
One of learning method which empower student and KBK appropriate is take advantage school yard as learning media at MA. Bahrul Ulum Mayang Jember. This research using based action reseach which consist four phase, that is planning, action, observation and reflection. That phases is a cycle with a spiral according to Kemmis and Taggart (1990). The output research data analysised by deskriptif kualitatif. The research achievement show average percentage increase after using shool yard as learning media.Keywords : School yard, Learning and teaching method, Student achievement